Topology of penicillin-binding protein 1b of Escherichia coli and topography of four antigenic determinants studied by immunocolabeling electron microscopy. - den Blaauwen, T (1990)
A method has been developed to study the orientation of proteins in the cytoplasmic membrane of Escherichia coli. Vesicles from sonicated cells were incubated in droplets on electron microscope support grids in sequence with a monoclonal antibody (MAb) against a protein with an unknown orientation (PBP 1b) followed by a MAb against a periplasmic component (peptidoglycan). The different MAbs were made visible with 5- and 10-nm gold-conjugated secondary antibodies, respectively. PBP 1b appeared to colabel with peptidoglycan. The labeling of PBP 1b in membrane vesicles with MAbs against four different epitopes was further used to estimate the number of PBP 1b molecules per cell. Approximately 1,400 PBP 1b molecules per cell grown in broth were labeled. The spatial distribution of the epitopes of the MAbs was studied by immunocolabeling of pairs of MAbs and by competitive antibody-binding inhibition. It could be tentatively concluded that the four epitopes form a cluster of antigenic determinants which occupy less than half of the surface of PBP 1b.